2004
DOI: 10.1111/j.0959-9673.2004.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proteasome inhibitors MG132, ZL3VS and AdaAhx3L3VS on protein metabolism in septic rats

Abstract: Proteasome inhibitors are novel therapeutic agents for the treatment of cancer and other severe disorders. One of the possible side effects is influencing the metabolism of proteins. The aim of our study was to evaluate the influence of three proteasome inhibitors MG132, ZL(3)VS and AdaAhx(3)L(3)VS on protein metabolism and leucine oxidation in incubated skeletal muscle of control and septic rats. Total proteolysis was determined according to the rates of tyrosine release into the medium during incubation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
11
20
0
Order By: Relevance
“…These data correspond with those reporting a lowering of protein synthesis in EDL following an LLnL treatment (16). Similar changes both in EDL and SOL were observed using MG132 and AdaAhx 3 L 3 VS, respectively (17,18). In contrast, LLnL has no effect on protein synthesis in incubated diaphragm (33).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data correspond with those reporting a lowering of protein synthesis in EDL following an LLnL treatment (16). Similar changes both in EDL and SOL were observed using MG132 and AdaAhx 3 L 3 VS, respectively (17,18). In contrast, LLnL has no effect on protein synthesis in incubated diaphragm (33).…”
Section: Discussionsupporting
confidence: 89%
“…A similar effect of AdaAhx 3 L 3 VS was demonstrated in both muscle types (17). We assume that this effect reflects a muscle-type-dependent response to belactosins rather than a decrease in total proteolysis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In fact, the relative contribution of ATP, Ca 2ϩ -dependent, and lysosomal proteolytic systems to adult skeletal muscle proteolysis was assessed by incubation of lumbrical muscles with inhibitors of proteasome (MG132) (27), calpain (leupeptin and E64) (55), and lysosome (methylamine) systems. Our results clearly showed that the proteasome system is the major route of protein degradation in adult skeletal muscle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the up‐regulation of autophagy and lysosomal genes has been documented at the transcript and protein levels in various catabolic conditions 76. There are reports demonstrating that muscles composed mostly by white fibres are more sensitive to catabolic stimuli, particularly to sepsis, when compared with muscles with high content of red fibres 77, 78. Also with advancing age, there is a preferential atrophy of white fibres 79.…”
Section: Hmb As a Nutritional Supplementmentioning
confidence: 99%